Parasites of Arctic char (Salvelinus alpinus) in North America: a systematic literature review and an analysis of contemporary data from anadromous populations from Nunavut - Les N. Harris; Phillip R. Morrison; Michael W. Johnson; Sara Bolduc; Ariane Côté; Amélie Papillon; Justine Lapointe; Xuehan Qu; David J. Yurkowski; Connor W. Faulkner; Colin P. Gallagher; Lauren N. Wiens; et al. (Reviews in Fish Biology and Fisheries, 2026)
Parasites play a critical yet understudied role in Arctic ecosystems, particularly within key subsistence species such as Arctic char ( Salvelinus alpinus ). As the Arctic undergoes rapid climate-driven change, establishing baseline parasite biodiversity is essential for monitoring ecological shifts and anticipating emerging health and conservation concerns. This study provides the most comprehensive assessment to date of Arctic char parasites in the North American Arctic by integrating a systematic literature review with new empirical data from 378 Arctic char collected across five Nunavut areas (2020–2024). The literature review (30 studies, 1956–2024) documented 67 parasite taxa—48 identified to species—with helminths (nematodes, cestodes, trematodes, acanthocephalans) dominant. Overall, 82% of taxa occurred in anadromous Arctic char and 54% in freshwater forms, including 22 species unique to anadromous fish. Our empirical assessment identified 35 parasite taxa—23 to species level—including several previously unreported from Arctic char in this region. Common and widespread parasites documented in the empirical assessment included Brachyphallus crenatus , Derogenes varicus , Bothrimonus sturionis , and Alloopistholecithum gibbosum , although notable spatial variation occurred in community composition and infection intensity. The occurrence of rare and previously unreported parasites may suggest emerging shifts in host–parasite dynamics potentially linked to changing prey availability and northward species range expansions. Together, these findings establish an essential baseline for Arctic char parasite biodiversity and highlight the need for continued monitoring to track future changes driven by climate warming, shifting food webs, and their implications for fish health and food security in northern Indigenous communities.

Digital design optimization and off-site modularization for modern stone masonry construction - Jian Zhang; Kavinda Isuru Nanayakkara; Linwei He; Helen Fairclough; Andrew Liew; Colin Smith; Matthew Gilbert (Engineering Structures, 2026)

The role of leaf morphological plasticity in maintaining crown condition: A case study of London plane (Platanus x acerifolia) and valley oak (Quercus lobata) - Mickie Tang; Matthew E. Gilbert; Emily K. Meineke (Urban Forestry & Urban Greening, 2025)

Using stochastically generated skewed distributions to represent hourly nontidal residual water levels at United States tide gauges - Paige A. Hovenga; Matthew Newman; John R. Albers; William Sweet; Gregory Dusek; Tongtong Xu; John A. Callahan; Sang-Ik Shin; Gilbert P. Compo (Frontiers in Marine Science, 2025)
The daily likelihood of High Tide Flooding (HTF) predicted by the National Oceanic and Atmospheric Administration (NOAA) for leads up to one year is expressed as the sum of a long-term trend, tides, and nontidal residuals (NTRs) whose probability density functions (PDFs) are assumed to be Gaussian (i.e., normally distributed). We analyzed observed detrended hourly NTR distributions at 148 NOAA tide gauges along the U.S. coastline and show that 98.7% of them are better characterized by ‘Stochastically Generated Skewed’ (SGS) distributions, a class of non-Gaussian (skewed, heavy-tailed) PDFs. In contrast to other methods that generate PDFs by fitting observed raw histograms, SGS distributions are determined through time series analysis. Observations are fit to a simple linear (autoregressive) time series model, driven by stochastic noise with a linear dependence upon the NTR anomaly. The PDF is then determined from the fitted model parameters. The SGS distributions improve upon the Gaussian PDF high-water probabilities at varying thresholds throughout the year along all U.S. coasts, with significantly better estimates along the U.S. East and Gulf coasts during summer (apart from large hurricane events) and along the U.S. West Coast during winter (even though variability there is often dominated by monthly time scales and many locations have nearly Gaussian PDFs). For evaluating extreme high-water event probabilities, the SGS distribution is no more sensitive to limited observations than kernel density estimation or Generalized Extreme Value methods. Tail probabilities for all three methods are generally similar. Our results may contribute to more robust and accurate HTF forecasts and, more broadly, provide additional insight in developing adaptation and mitigation strategies for future sea level conditions.

Arctic lake trout ( Salvelinus namaycush ) show evidence of seasonal acclimation of cardiac adrenergic sensitivity but not heat tolerance - Emily P. Williams; Les N. Harris; Jean‐Sébastien Moore; Ella K. Middleton; Shira A. Berkelhammer; Ben Speers‐Roesch; Matthew J. H. Gilbert (Journal of Fish Biology, 2025)
Many Arctic fishes experience prolonged periods of extreme cold and large thermal variation over both rapid and seasonal time scales which challenge critical physiological functions. In the central Canadian Arctic, we caught wild adult lake trout ( Salvelinus namaycush ) acclimatized to winter and summer temperatures to determine the extent to which they seasonally adjust cardiac thermal performance and adrenergic control. We assessed the intrinsic and maximum heart rate ( f Hint and f Hmax ) of anaesthetised fish through cholinergic blockade and either adrenergic blockade ( f Hint ) or stimulation ( f Hmax ) during acute warming. Contrary to expectations, S. namaycush showed largely consistent heart rate responses to acute warming between seasons and adrenergic treatments. The f Hmax increased with acute warming and reached a peak (peak f H ) of 83 and 93 beats min −1 at temperatures ( T peak ) of 19.6 and 20°C and arrhythmia occurred at temperatures ( T arr ) of 22.7 and 22.3°C in winter and summer, respectively. However, in the winter, adrenergic stimulation was important to achieve peak f H at high temperatures; adrenergic blockade in winter did not affect T peak (18.3°C) or T arr (21°C) but lowered peak f H to only 68 beats min −1 ( p f H , when compared at common, cool to moderate temperatures, winter acclimated fish did exhibit slower atrioventricular conduction (longer PR interval), slower ventricular depolarization (longer QRS duration) and a shorter overall systolic duration (lower QT interval). Overall, S. namaycush exhibited no seasonal plasticity in cardiac thermal tolerance and modest seasonal changes in adrenergic control at high temperatures and in cardiac electrical activity. This limited thermal plasticity may constrain their ability to cope with seasonally distinct thermal challenges including extreme heat events and increase their reliance on other coping or avoidance mechanisms when thermal refugia are available (e.g. behavioural thermoregulation). An increased need for avoidance behaviour could limit the accessibility of key habit for foraging and spawning which occurs in late summer in this region (Dubos et al., 2024).

Migratory Arctic char ( Salvelinus alpinus ) as a prey pulse for Arctic marine predators - Matthew J. H. Gilbert; Les N. Harris; Alexander L. Vail; Kristin L. Laidre; Mark L. Mallory; David J. Yurkowski (Ecology, 2025)

Minimum material vault designs generated via adaptive layout optimization - Linwei He; Helen E. Fairclough; Matthew Gilbert; Andrew Liew; Karol Bołbotowski (Engineering Structures, 2025)

Evaluating the Efficacy of Drone‐Based Thermal Images for Measuring Wildlife Abundance and Physiology - Wade A. Matern; Abram B. Fleishman; Ianna Gilbert; Xaun Wilson; Jean‐Marc Beddow; Isabella Garfield; Armando Ornelas; Matthew McKown; Patrick W. Robinson; Roxanne S. Beltran (Marine Mammal Science, 2025)
Although drones are a promising alternative to traditional wildlife monitoring methods, validation efforts are needed to quantify the accuracy of abundance and distribution estimates obtained from using drones. We used drones equipped with high‐resolution Red‐Green‐Blue (RGB) and thermal cameras, coupled with machine learning techniques, to assess the abundance and thermal physiology in northern elephant seals ( Mirounga angustirostris ). Aerial images of 3415 seals and measurements of ambient air temperature, wind speed, and time of day were collected during nighttime and daytime drone flights ( N = 24). Two‐dimensional polygons and surface temperatures of seals were measured from the images. Machine learning algorithms were applied to detect seals in the imagery, and model performance was evaluated. Detection was more accurate using RGB images (machine learning averaged 6.8% lower than human counts) than thermal images (16.6%). However, thermal images were useful for determining that time of day and ambient temperature (but not wind speed or body size) influenced seal external skin temperature. RGB and thermal cameras have different strengths and weaknesses that should be considered when designing research studies. Our study demonstrates that integrating drones, thermal imaging, and machine learning can promote faster, safer, cheaper, less disruptive, and more accurate wildlife monitoring and conservation efforts.

Identifying the influence of hydroclimatic factors on streamflow: A multi-model data-driven approach - Khandaker Iftekharul Islam; James Matthew Gilbert (Journal of Hydrology, 2025)

The potential of oviduct tags and fine‐scale acoustic telemetry to reveal the timing and location of spawning in Arctic salmonids ( Salvelinus spp.) - Véronique Dubos; Les N. Harris; Richard Ekpakohak; Brendan K. Malley; Matthew J. H. Gilbert; Nathan B. Furey; Jean‐Sébastien Moore (Journal of Fish Biology, 2025)
Identifying and characterizing spawning locations are paramount for the protection of critical fish habitats but can be challenging, particularly in remote locations. Using the underexplored oviduct‐tagging technique, we aimed to identify the timing and location of spawning for wild Arctic char ( Salvelinus alpinus ) and lake trout ( Salvelinus namaycush ) in two high‐Arctic lakes in Nunavut. Specifically, Innovasea V7 acoustic telemetry transmitters were inserted into the oviducts of 13 Arctic char and 4 lake trout, and the timing and location of tag expulsion were determined using a fine‐scale positioning system. Twenty Arctic char and 20 lake trout were also tagged with abdominal V16 transmitters, and 10 of them were paired with the oviduct tags, to further study the behavior of individual fish during the spawning season. Oviduct tags from four Arctic char and one lake trout could be used to assess the timing and location of spawning. Spawning anadromous Arctic char drastically reduced their activity and remained proximate to their presumed spawning location immediately before and for months after spawning. In contrast, a non‐anadromous (i.e., freshwater resident) Arctic char and a lake trout showed little to no reduction in activity around presumed spawning events. Because of the highlighted sedentary behavior of inferred spawning anadromous Arctic char implanted with both abdominal and oviduct tags, we could also infer potential spawning based on the behavior of individuals equipped only with abdominal tags. Spawning areas identified via telemetry also aligned well with Inuit knowledge of those lakes. This is the first field study to use acoustic oviduct and abdominal tags coupled with a fine‐scale positioning system. Despite a limited success rate of ejection, the study reveals the strong potential of the method to study spawning habitat and timing, particularly in remote areas.

Comparison of ground-structure and continuum based topology optimization methods for strut-and-tie model generation - Yi Xia; Andrew Liew; Hongfei Wu; Matthijs Langelaar; Max A.N. Hendriks; Yuanlong Yang; Meisam Takalloozadeh; Matthew Gilbert (Engineering Structures, 2024)

The 3d response of a large-scale masonry arch bridge - part I: Performance under low and medium loading levels - Vasilis Sarhosis; Bowen Liu; Matthew Gilbert (Engineering Structures, 2024)

The 3D response of a large-scale masonry arch bridge – Part II: Performance at failure - Bowen Liu; Vasilis Sarhosis; Adam D. Booth; Matthew Gilbert (Engineering Structures, 2024)

Microplastic and other anthropogenic microparticles in Arctic char (Salvelinus alpinus) and their coastal habitat: A first-look at a central Canadian Arctic commercial fishery - Bonnie M. Hamilton; Les N. Harris; Beverly Maksagak; Emilie Nero; Matthew J.H. Gilbert; Jennifer F. Provencher; Chelsea M. Rochman (Science of The Total Environment, 2024)

A multispecies hierarchical model to integrate count and distance‐sampling data - Neil A. Gilbert; Caroline M. Blommel; Matthew T. Farr; David S. Green; Kay E. Holekamp; Elise F. Zipkin (Ecology, 2024)
Integrated community models—an emerging framework in which multiple data sources for multiple species are analyzed simultaneously—offer opportunities to expand inferences beyond the single‐species and single‐data‐source approaches common in ecology. We developed a novel integrated community model that combines distance sampling and single‐visit count data; within the model, information is shared among data sources (via a joint likelihood) and species (via a random‐effects structure) to estimate abundance patterns across a community. Parameters relating to abundance are shared between data sources, and the model can specify either shared or separate observation processes for each data source. Simulations demonstrated that the model provided unbiased estimates of abundance and detection parameters even when detection probabilities varied between the data types. The integrated community model also provided more accurate and more precise parameter estimates than alternative single‐species and single‐data‐source models in many instances. We applied the model to a community of 11 herbivore species in the Masai Mara National Reserve, Kenya, and found considerable interspecific variation in response to local wildlife management practices: Five species showed higher abundances in a region with passive conservation enforcement (median across species: 4.5× higher), three species showed higher abundances in a region with active conservation enforcement (median: 3.9× higher), and the remaining three species showed no abundance differences between the two regions. Furthermore, the community average of abundance was slightly higher in the region with active conservation enforcement but not definitively so (posterior mean: higher by 0.20 animals; 95% credible interval: 1.43 fewer animals, 1.86 more animals). Our integrated community modeling framework has the potential to expand the scope of inference over space, time, and levels of biological organization, but practitioners should carefully evaluate whether model assumptions are met in their systems and whether data integration is valuable for their applications.

Development of a culturally targeted chatbot to inform living kidney donor candidates of African ancestry about APOL1 genetic testing: a mixed methods study - Elisa J. Gordon; Jessica Gacki-Smith; Matthew J. Gooden; Preeya Waite; Rochell Yacat; Zenab R. Abubakari; Debra Duquette; Akansha Agrawal; John Friedewald; Sarah K. Savage; Matthew Cooper; Alexander Gilbert; et al. (Journal of Community Genetics, 2024)
Clinical chatbots are increasingly used to help integrate genetic testing into clinical contexts, but no chatbot exists for A polipoprotein L1 ( APOL1 ) genetic testing of living kidney donor (LKD) candidates of African ancestry. Our study aimed to culturally adapt and assess perceptions of the Gia® chatbot to help integrate APOL1 testing into LKD evaluation. Ten focus groups and post-focus group surveys were conducted with 54 LKDs, community members, and kidney transplant recipients of African ancestry. Data were analyzed through thematic analysis and descriptive statistics. Key themes about making Gia culturally targeted included ensuring: (1) transparency by providing Black LKDs’ testimonials, explaining patient privacy and confidentiality protections, and explaining how genetic testing can help LKD evaluation; (2) content is informative by educating Black LKDs about APOL1 testing instead of aiming to convince them to undergo testing, presenting statistics, and describing how genetic discrimination is legally prevented; and (3) content avoids stigma about living donation in the Black community. Most agreed Gia was neutral and unbiased (82%), trustworthy (82%), and words, phrases, and expressions were familiar to the intended audience (85%). Our culturally adapted APOL1 Gia chatbot was well regarded. Future research should assess how this chatbot could supplement provider discussion prior to genetic testing to scale APOL1 counseling and testing for LKD candidate clinical evaluation.

Hydrodynamic response to bathymetric changes in Tampa Bay, Florida - Jing Chen; Yonggang Liu; Robert H. Weisberg; Steven A. Murawski; Sherryl Gilbert; David F. Naar; Lianyuan Zheng; Matthew Hommeyer; Catherine Dietrick; Mark E. Luther; Cheryl Hapke; Edward Myers; et al. (Deep Sea Research Part II: Topical Studies in Oceanography, 2023)

Experimental investigation on the shear behaviour of the brickwork-backfill interface in masonry arch bridges - Bowen Liu; Anastasios Drougkas; Vasilis Sarhosis; Colin C. Smith; Matthew Gilbert (Engineering Structures, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Animal Borne Ocean Sensors – AniBOS – An Essential Component of the Global Ocean Observing System - Clive R. McMahon; Fabien Roquet; Sophie Baudel; Mathieu Belbeoch; Sophie Bestley; Clint Blight; Lars Boehme; Fiona Carse; Daniel P. Costa; Michael A. Fedak; Christophe Guinet; Robert Harcourt; et al. (Frontiers in Marine Science, 2021)
Marine animals equipped with biological and physical electronic sensors have produced long-term data streams on key marine environmental variables, hydrography, animal behavior and ecology. These data are an essential component of the Global Ocean Observing System (GOOS). The Animal Borne Ocean Sensors (AniBOS) network aims to coordinate the long-term collection and delivery of marine data streams, providing a complementary capability to other GOOS networks that monitor Essential Ocean Variables (EOVs), essential climate variables (ECVs) and essential biodiversity variables (EBVs). AniBOS augments observations of temperature and salinity within the upper ocean, in areas that are under-sampled, providing information that is urgently needed for an improved understanding of climate and ocean variability and for forecasting. Additionally, measurements of chlorophyll fluorescence and dissolved oxygen concentrations are emerging. The observations AniBOS provides are used widely across the research, modeling and operational oceanographic communities. High latitude, shallow coastal shelves and tropical seas have historically been sampled poorly with traditional observing platforms for many reasons including sea ice presence, limited satellite coverage and logistical costs. Animal-borne sensors are helping to fill that gap by collecting and transmitting in near real time an average of 500 temperature-salinity-depth profiles per animal annually and, when instruments are recovered (∼30% of instruments deployed annually, n = 103 ± 34), up to 1,000 profiles per month in these regions. Increased observations from under-sampled regions greatly improve the accuracy and confidence in estimates of ocean state and improve studies of climate variability by delivering data that refine climate prediction estimates at regional and global scales. The GOOS Observations Coordination Group (OCG) reviews, advises on and coordinates activities across the global ocean observing networks to strengthen the effective implementation of the system. AniBOS was formally recognized in 2020 as a GOOS network. This improves our ability to observe the ocean’s structure and animals that live in them more comprehensively, concomitantly improving our understanding of global ocean and climate processes for societal benefit consistent with the UN Sustainability Goals 13 and 14: Climate and Life below Water. Working within the GOOS OCG framework ensures that AniBOS is an essential component of an integrated Global Ocean Observing System.

Leech blood‐meal invertebrate‐derived DNA reveals differences in Bornean mammal diversity across habitats - Rosie Drinkwater; Tommaso Jucker; Joshua H. T. Potter; Tom Swinfield; David A. Coomes; Eleanor M. Slade; M. Thomas P. Gilbert; Owen T. Lewis; Henry Bernard; Matthew J. Struebig; Elizabeth L. Clare; Stephen J. Rossiter (Molecular Ecology, 2021)
The application of metabarcoding to environmental and invertebrate‐derived DNA (eDNA and iDNA) is a new and increasingly applied method for monitoring biodiversity across a diverse range of habitats. This approach is particularly promising for sampling in the biodiverse humid tropics, where rapid land‐use change for agriculture means there is a growing need to understand the conservation value of the remaining mosaic and degraded landscapes. Here we use iDNA from blood‐feeding leeches ( Haemadipsa picta ) to assess differences in mammalian diversity across a gradient of forest degradation in Sabah, Malaysian Borneo. We screened 557 individual leeches for mammal DNA by targeting fragments of the 16S rRNA gene and detected 14 mammalian genera. We recorded lower mammal diversity in the most heavily degraded forest compared to higher quality twice logged forest. Although the accumulation curves of diversity estimates were comparable across these habitat types, diversity was higher in twice logged forest, with more taxa of conservation concern. In addition, our analysis revealed differences between the community recorded in the heavily logged forest and that of the twice logged forest. By revealing differences in mammal diversity across a human‐modified tropical landscape, our study demonstrates the value of iDNA as a noninvasive biomonitoring approach in conservation assessments.

Argo Data 1999–2019: Two Million Temperature-Salinity Profiles and Subsurface Velocity Observations From a Global Array of Profiling Floats - Annie P. S. Wong; Susan E. Wijffels; Stephen C. Riser; Sylvie Pouliquen; Shigeki Hosoda; Dean Roemmich; John Gilson; Gregory C. Johnson; Kim Martini; David J. Murphy; Megan Scanderbeg; T. V. S. Udaya Bhaskar; et al. (Frontiers in Marine Science, 2020)

Coronavirus surveillance of wildlife in the Lao People’s Democratic Republic detects viral RNA in rodents - David J. McIver; Soubanh Silithammavong; Watthana Theppangna; Amethyst Gillis; Bounlom Douangngeun; Kongsy Khammavong; Sinpakone Singhalath; Veasna Duong; Philippe Buchy; Sarah H. Olson; Lucy Keatts; Amanda E. Fine; et al. (Archives of Virology, 2020)

Measuring maximum oxygen uptake with an incremental swimming test and by chasing rainbow trout to exhaustion inside a respirometry chamber yields the same results - Yangfan Zhang; Matthew J. H. Gilbert; Anthony P. Farrell (Journal of Fish Biology, 2020)
This study hypothesized that oxygen uptake ( Ṁ O 2 ) measured with a novel protocol of chasing rainbow trout Oncorhynchus mykiss to exhaustion inside a static respirometer while simultaneously monitoring Ṁ O 2 ( Ṁ O 2chase ) would generate the same and repeatable peak value as when peak active Ṁ O 2 ( Ṁ O 2active ) is measured in a critical swimming speed protocol. To reliably determine peak Ṁ O 2chase , and compare to the peak during recovery of Ṁ O 2 after a conventional chase protocol outside the respirometer ( Ṁ O 2rec ), this study applied an iterative algorithm and a minimum sampling window duration ( i.e. , 1 min based on an analysis of the variance in background and exercise Ṁ O 2 ) to account for Ṁ O 2 dynamics. In support of this hypothesis, peak Ṁ O 2active (707 ± 33 mg O 2 h −1 kg −1 ) and peak Ṁ O 2chase (663 ± 43 mg O 2 h −1 kg −1 ) were similar ( P = 0.49) and repeatable (Pearson's and Spearman's correlation test; r ≥ 0.77; P Ṁ O 2max can be independent of whether a fish is exhaustively chased inside a respirometer or swum to fatigue in a swim tunnel, provided Ṁ O 2 is analysed with an iterative algorithm and a minimum but reliable sampling window. The importance of using this analytical approach was illustrated by peak Ṁ O 2chase being 23% higher ( P P Ṁ O 2chase was 18% higher ( P Ṁ O 2rec , chasing a fish inside a static respirometer may be a better protocol for obtaining maximum Ṁ O 2 .

Anadromy and marine habitat use of Lake trout ( Salvelinus namaycush ) from the central Canadian Arctic - Les N. Harris; Heidi K. Swanson; Matthew J.H. Gilbert; Brendan K. Malley; Aaron T. Fisk; Jean‐Sébastien Moore (Journal of Fish Biology, 2020)
Anadromy was documented in 16 lake trout, Salvelinus namaycush , from Canada's central Arctic using capture data and otolith microchemistry. For the first time, estuarine/marine habitat use was described for five individuals using acoustic telemetry. Age‐at‐first‐migration to sea was variable (10–39 years) among individuals and most S. namaycush undertook multiple anadromous migrations within their lifetime. Telemetry data suggested that S. namaycush do not travel far into marine habitats and prefer surface waters ( S. namaycush .

Detecting spiny dogfish in grey seal diets - Kathryn A. Ono; Cathleen M. Steinbeiser; Austin B. Coco; Matthew J. Sheehan; Abigail J. Beck; Michelle N. Dufault; Katelyn M. Gilbert; Jessica J. Antonez; Zachary H. Olson (Conservation Genetics Resources, 2019)

Killer whale genomes reveal a complex history of recurrent admixture and vicariance - Andrew D. Foote; Michael D. Martin; Marie Louis; George Pacheco; Kelly M. Robertson; Mikkel‐Holger S. Sinding; Ana R. Amaral; Robin W. Baird; Charles Scott Baker; Lisa Ballance; Jay Barlow; Andrew Brownlow; et al. (Molecular Ecology, 2019)
Reconstruction of the demographic and evolutionary history of populations assuming a consensus tree‐like relationship can mask more complex scenarios, which are prevalent in nature. An emerging genomic toolset, which has been most comprehensively harnessed in the reconstruction of human evolutionary history, enables molecular ecologists to elucidate complex population histories. Killer whales have limited extrinsic barriers to dispersal and have radiated globally, and are therefore a good candidate model for the application of such tools. Here, we analyse a global data set of killer whale genomes in a rare attempt to elucidate global population structure in a nonhuman species. We identify a pattern of genetic homogenisation at lower latitudes and the greatest differentiation at high latitudes, even between currently sympatric lineages. The processes underlying the major axis of structure include high drift at the edge of species' range, likely associated with founder effects and allelic surfing during postglacial range expansion. Divergence between Antarctic and non‐Antarctic lineages is further driven by ancestry segments with up to four‐fold older coalescence time than the genome‐wide average; relicts of a previous vicariance during an earlier glacial cycle. Our study further underpins that episodic gene flow is ubiquitous in natural populations, and can occur across great distances and after substantial periods of isolation between populations. Thus, understanding the evolutionary history of a species requires comprehensive geographic sampling and genome‐wide data to sample the variation in ancestry within individuals.

RNA interference-based silencing of the alpha-amylase (amy1) gene in Aspergillus flavus decreases fungal growth and aflatoxin production in maize kernels - Matthew K. Gilbert; Rajtilak Majumdar; Kanniah Rajasekaran; Zhi-Yuan Chen; Qijian Wei; Christine M. Sickler; Matthew D. Lebar; Jeffrey W. Cary; Bronwyn R. Frame; Kan Wang (Planta, 2018)

Evaluation of eDNA for groundwater invertebrate detection and monitoring: a case study with endangered Stygobromus (Amphipoda: Crangonyctidae) - Matthew L. Niemiller; Megan L. Porter; Jenna Keany; Heather Gilbert; Daniel W. Fong; David C. Culver; Christopher S. Hobson; K. Denise Kendall; Mark A. Davis; Steven J. Taylor (Conservation Genetics Resources, 2018)

Naturally occurring high oleic acid cottonseed oil: identification and functional analysis of a mutant allele of Gossypium barbadense fatty acid desaturase-2 - Jay Shockey; Michael Dowd; Brian Mack; Matthew Gilbert; Brian Scheffler; Linda Ballard; James Frelichowski; Catherine Mason (Planta, 2017)

Identifying gene–gene interactions that are highly associated with four quantitative lipid traits across multiple cohorts - Rishika De; Shefali S. Verma; Emily Holzinger; Molly Hall; Amber Burt; David S. Carrell; David R. Crosslin; Gail P. Jarvik; Helena Kuivaniemi; Iftikhar J. Kullo; Leslie A. Lange; Matthew B. Lanktree; et al. (Human Genetics, 2017)

The role of substrate holding in achieving critical swimming speeds: a case study using the invasive round goby (Neogobius melanostomus) - Matthew J. H. Gilbert; Janelle M. Barbarich; Matthew Casselman; Ashley V. Kasurak; Dennis M. Higgs; Keith B. Tierney (Environmental Biology of Fishes, 2016)

Hydrodynamic Radii of Ranibizumab, Aflibercept and Bevacizumab Measured by Time-Resolved Phosphorescence Anisotropy - Liisa M. Hirvonen; Gilbert O. Fruhwirth; Nishanthan Srikantha; Matthew J. Barber; James E. Neffendorf; Klaus Suhling; Timothy L. Jackson (Pharmaceutical Research, 2016)

Widespread Chemical Detoxification of Alkaloid Venom by Formicine Ants - Edward G. LeBrun; Peter J. Diebold; Matthew R. Orr; Lawrence E. Gilbert (Journal of Chemical Ecology, 2015)

Development and analysis of a highly flexible multi-gene expression system for metabolic engineering in Arabidopsis seeds and other plant tissues - Jay Shockey; Catherine Mason; Matthew Gilbert; Heping Cao; Xiangjun Li; Edgar Cahoon; John Dyer (Plant Molecular Biology, 2015)

Mapping a region within the 1RS.1BL translocation in common wheat affecting grain yield and canopy water status - Tyson Howell; Iago Hale; Ljupcho Jankuloski; Marcos Bonafede; Matthew Gilbert; Jorge Dubcovsky (Theoretical and Applied Genetics, 2014)

Multivariate Analysis of an LA-ICP-MS Trace Element Dataset for Pyrite - Lyron Winderbaum; Cristiana L. Ciobanu; Nigel J. Cook; Matthew Paul; Andrew Metcalfe; Sarah Gilbert (Mathematical Geosciences, 2012)

Helping Gulf Shrimpers Adopt Safety Measures: Importance of Partnerships and Research to Practice - Jeffrey L. Levin; Karen Gilmore; Ann Carruth; Amanda Wickman; Sara Shepherd; Gilbert Gallardo; Matthew Nonnenmann (Journal of Agromedicine, 2012)

Factors Influencing Safety Among a Group of Commercial Fishermen Along the Texas Gulf Coast - Jeffrey L. Levin; Karen Gilmore; Sara Shepherd; Amanda Wickman; Ann Carruth; J. Torey Nalbone; Gilbert Gallardo; Matthew W. Nonnenmann (Journal of Agromedicine, 2010)

A multidisciplinary study of archaeological grape seeds - Enrico Cappellini; M. Thomas P. Gilbert; Filippo Geuna; Girolamo Fiorentino; Allan Hall; Jane Thomas-Oates; Peter D. Ashton; David A. Ashford; Paul Arthur; Paula F. Campos; Johan Kool; Eske Willerslev; et al. (The Science of Nature, 2010)

A “GC-rich” method for mammalian gene expression: A dominant role of non-coding DNA GC content in regulation of mammalian gene expression - Qian Jia; HongTao Wu; XingJun Zhou; Jian Gao; Wei Zhao; JouDi Aziz; JingShuang Wei; Lihua Hou; Shuyin Wu; Ying Zhang; XiangFeng Dong; YanMin Huang; et al. (Science China Life Sciences, 2010)

The growth responses of coastal dune species are determined by nutrient limitation and sand burial - Matthew Gilbert; Norman Pammenter; Brad Ripley (Oecologia, 2008)